OPTIMIZING DIGITAL MARKETING TO INCREASE SALES OF MICRO BUSINESSES IN THE CULINARY SECTOR IN GORONTALO CITY - Iko, Sindi Yanti; Wolok, Tineke; Monoarfa, Mohamad Agus Salim (JAMBURA: Jurnal Ilmiah Manajemen dan Bisnis, 2026)
This study aims to determine the effect of Digital Marketing utilization on the sales level of Micro Businesses in the Culinary Sector in Gorontalo City. This study uses a quantitative research method, and the data used are the results of questionnaires from 96 MSME respondents. The data analysis used in this study is simple linear regression. The results of the study indicate that the use of digital marketing has a positive and significant effect on increasing sales. These findings indicate that the more optimally businesses use digital marketing, the more they are able to boost sales. In addition, this study also confirms that most of the variation in sales growth can be explained by the use of digital marketing, while the rest is influenced by other factors that are not the focus of this study.